An Analysis of Educational Value in Fall Movie - Kasriyati , Destina; Rulliza, Anni; Jaufani, Asma; Lestari , Winda (English Language and Education Spectrum, 2024)
The study's goals were to determine the advantages of watching movies and their educational worth. The source of the movie discussed in this research is: Educational Value in Fall Movie. There were two sources of data used in this thesis. The main data source was obtained from the movie in the form of dialogue scripts between characters in the movie. The second data was obtained from articles related to research and other sources from the internet. The type of research in this movie was descriptive qualitative. It was used to answer the questions in problem of the research and was presented in the form of a description. Based on the analysis, it was known that there were several educational values found, including: honest, brave, love and affection, respect, discipline, kind and friendly, fair and humanist. In addition, there were two benefits of watching Movie: An Analysis of Educational Value in Fall Movie, namely: as medium of education and medium of entertainment.